2020
DOI: 10.1101/2020.12.18.423392
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The bacterial virulence factors rhamnolipids and their (R)-3-hydroxyalkanoate precursors activateArabidopsisinnate immunity through two independent mechanisms

Abstract: Plant innate immunity is activated upon perception of invasion pattern molecules by plant cell-surface immune receptors. Several bacteria of the genera Pseudomonas and Burkholderia produce rhamnolipids (RLs) from L- rhamnose and (R)-3-hydroxyalkanoate precursors (HAAs). RL and HAA secretion is required to modulate bacterial surface motility, biofilm development, and thus successful colonization of hosts. Here, we show that the lipidic secretome from the opportunistic pathogen Pseudomonas aeruginosa mostly comp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 83 publications
(105 reference statements)
0
1
0
Order By: Relevance
“…Indeed, many danger signals or invasion patterns are recognized by specific pattern recognition receptors within PPM (Pršić & Ongena, 2020;Schellenberger et al, 2019), and some amphiphilic elicitors, like surfactin from Bacillus and rhamnolipids (RLs) from Pseudomonas, have been strongly suggested to be perceived by the lipid fraction of PPM (Come et al, 2021;Gerbeau-Pissot et al, 2014;Haba et al, 2014;Henry et al, 2011;Herzog et al, 2020;Luzuriaga-Loaiza et al, 2018;Monnier et al, 2018). Very recently, it was also demonstrated that the RL-triggered immune response is independent of the LORE receptor and is affected by the sphingolipid composition of the plasma membrane suggesting a direct interaction of RLs with plant plasma membrane lipids (Schellenberger et al, 2021), similar to what has been shown on membrane models (Luzuriaga-Loaiza et al, 2018).…”
Section: •−mentioning
confidence: 99%
“…Indeed, many danger signals or invasion patterns are recognized by specific pattern recognition receptors within PPM (Pršić & Ongena, 2020;Schellenberger et al, 2019), and some amphiphilic elicitors, like surfactin from Bacillus and rhamnolipids (RLs) from Pseudomonas, have been strongly suggested to be perceived by the lipid fraction of PPM (Come et al, 2021;Gerbeau-Pissot et al, 2014;Haba et al, 2014;Henry et al, 2011;Herzog et al, 2020;Luzuriaga-Loaiza et al, 2018;Monnier et al, 2018). Very recently, it was also demonstrated that the RL-triggered immune response is independent of the LORE receptor and is affected by the sphingolipid composition of the plasma membrane suggesting a direct interaction of RLs with plant plasma membrane lipids (Schellenberger et al, 2021), similar to what has been shown on membrane models (Luzuriaga-Loaiza et al, 2018).…”
Section: •−mentioning
confidence: 99%